Obvezni primjerak tiskanih knjiga u Nacionalnoj i sveučilišnoj knjižnici u Zagrebu – iskaz nacionalne nakladničke produkcije - Krpan Smiljanec, Marina (Knjižnica, 2020)
Purpose: The aim of the work is to explore, present and observe the role of the legal deposit of printed book as a statement of national (i.e. territorial-state) imprint production, which is the basis of national heritage and to show the conducted critical analysis of the conceptual scope and potentional reach of the legal deposit of printed book.Methodology/approach: The research is based on the defined criteria made on a legal deposit of the printed books at the National and university library in Zagreb for the pe-riod from 2015. to 2018. For the purpose of this work, the traditional research approach is aimed at qualitative and quantitative methods and historical and descriptive in the statement of the historical background of the emergence and development of the legal deposit.Results: Conducted research indicates that the existing models of statistical data pro-cessing do not present national printed production.Originality/practical implications: Originality is present in the fact that it is the first such analysis of the stated objective and proposed models can serve as guidelines for the development of improved statistical solutions.
Keywords: Hrvaška; knjižnično gradivo; nacionalne knjižnice; obvezni izvodi